2021
DOI: 10.3389/fpsyg.2021.634543
|View full text |Cite
|
Sign up to set email alerts
|

Dehumanization During the COVID-19 Pandemic

Abstract: Communities often unite during a crisis, though some cope by ascribing blame or stigmas to those who might be linked to distressing life events. In a preregistered two-wave survey, we evaluated the dehumanization of Asians and Asian Americans during the COVID-19 pandemic. Our first wave (March 26–April 2, 2020; N = 917) revealed dehumanization was prevalent, between 6.1% and 39% of our sample depending on measurement. Compared to non-dehumanizers, people who dehumanized also perceived the virus as less risky t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…Disgust toward Chinese people, in turn, predicted greater blatant dehumanization of them. Understanding the factors shaping such blatant dehumanization may be paramount to addressing the discrimination and violence faced by Chinese people and other Asians in the USA during the COVID-19 pandemic (Croucher et al, 2020 ; Tavernese & Oppel Jr., 2020 ; see also Markowitz et al, 2021 ). However, for the purposes of establishing a generalizable model of prophylactic dehumanization, our focus on this single population can be seen as a limitation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Disgust toward Chinese people, in turn, predicted greater blatant dehumanization of them. Understanding the factors shaping such blatant dehumanization may be paramount to addressing the discrimination and violence faced by Chinese people and other Asians in the USA during the COVID-19 pandemic (Croucher et al, 2020 ; Tavernese & Oppel Jr., 2020 ; see also Markowitz et al, 2021 ). However, for the purposes of establishing a generalizable model of prophylactic dehumanization, our focus on this single population can be seen as a limitation.…”
Section: Resultsmentioning
confidence: 99%
“…In the USA, influential politicians and media outlets implicated China in the pandemic, and Chinese-Americans were verbally abused and physically attacked (Tavernese & Oppel Jr., 2020 ). In fact, some even blatantly dehumanized Chinese people (Markowitz et al, 2021 ). Therefore, beginning the day President Trump announced the pandemic was a national public health crisis (March 13, 2020; AMJC, 2020 ), we tested the Prophylactic Dehumanization Model among a sample of Americans.…”
Section: Re-analysis Of Nazi Propagandamentioning
confidence: 99%
“…In the USA, influential politicians and media outlets implicated China in the pandemic, and Chinese-Americans were verbally abused and physically attacked (Tavernese & Oppel Jr., 2020). In fact, some even blatantly dehumanized Chinese people (Markowitz et al, 2021). Therefore, beginning the day President Trump announced the pandemic was a national public health crisis (March 13, 2020; AMJC, 2020), we tested the Prophylactic Dehumanization Model among a sample of Americans.…”
Section: Studymentioning
confidence: 99%
“…Blame is a feature of individual, organizational, system and government responses to COVID-19 pandemic worldwide. Struggling to deal with an invisible, organic threat, many governments, agencies, and individuals have sought instead to assign undue responsibility of the spread of COVID-19 to groups and entire countries (e.g., China; Al-Jazeera, 2020 ), minority groups ( Sarkar, 2020 ; Markowitz et al, 2021 ). The World Health Organization has suggested that the language used around pandemics is critical to limiting blame and stigma, but many world leaders have paid no heed to this advice, calling COVID-19 by regional language or variants by their location of origin ( World Health Organisation [WHO], 2020 ).…”
Section: Introductionmentioning
confidence: 99%